Inactivation of the p15 gene in children with acute lymphoblastic leukemia - Cipolotti, Rosana; Lemos, José Alexandre Rodrigues; Defavery, Ricardo; Scrideli, Carlos Alberto; Fabbro, Amaury Lellis Dal; Tone, Luiz Gonzaga (São Paulo Medical Journal, 2003)
CONTEXT: Tumor suppressor genes act on the control of cell cycle progression. In pediatric neoplasias, some of these genes may be considered to be markers for diagnosis or relapse, thus probably representing prognostic indicators. OBJECTIVE: To study the inactivation of the p15 gene in children with acute lymphoblastic leukemia. TYPE OF STUDY: Retrospective study. SETTING: Laboratory of Molecular Biology, Department of Pediatrics, Faculdade de Medicina de Ribeirão Preto, Universidade de São Paulo. PARTICIPANTS: Eighty-three children and adolescents with acute lymphoblastic leukemia were studied, with the examination of 83 bone marrow samples obtained at diagnosis, four obtained also during relapse, and two cerebrospinal fluid samples obtained from two cases of isolated relapse in the central nervous system. MAIN MEASUREMENTS: Homologous deletion of the p15 gene by multiplex polymerase chain reaction, and screening for point mutations by polymerase chain reaction/single-strand conformational polymorphism. RESULTS: Deletion of exon 2 of the p15 gene was observed in 15 children, including one case in which deletion was only verified during isolated central nervous system relapse. No case of exon 1 deletion, or that was suggestive of point mutations, was observed and no association between p15 gene inactivation and classic risk factors was established. CONCLUSION: According to the literature, inactivation of the p15 gene by deletion of exon 2 in acute lymphoblastic leukemia found in the population studied would be considered to be a molecular marker for diagnosis or relapse. However, no correlation between p15 gene deletion and clinical prognostic indicators was observed.